L'Intelligence Émotionnelle du Leadership Informel dans les Contextes des Sports Collectifs: Une Approche Théorique - Brir, Hicham (International Journal of Education, Management, and Technology, 2025)
This theoretical study examines the pivotal role of emotional intelligence (EI) in the emergence of informal leadership within team sports. Drawing on Mayer and Salovey's (1997) and Goleman's (1995) frameworks, we demonstrate how emotional competencies enable certain athletes to exert significant informal influence, regardless of their official status. Three key mechanisms are identified: (1) regulation of collective emotions in competitive stress situations (Laborde et al., 2016), (2) mediation of interpersonal conflicts (Wagstaff et al., 2017), and (3) optimization of nonverbal communication (Furley & Schweizer, 2014). The analysis reveals that these informal leaders, described as "emotional conductors" by Fransen et al. (2015), build their legitimacy through nuanced understanding of group affective dynamics. However, as highlighted by Cotterill and Fransen (2016), this influence operates within a complex ecosystem combining individual factors, interpersonal relationships and organizational context. The article suggests practical applications for athlete training and proposes future research directions to better understand cultural and situational variations of these phenomena.